C4d in lupus nephritis and correlation with clinicopathologic findings - Tahereh Malakoutian; Atefeh Amouzegar; Mojgan Asgari; Tina Shooshtarizadeh (Society of Diabetic Nephropathy Prevention, 2018)
Background: Lupus nephritis (LN) is a serious complication of systemic lupus erythematosus (SLE). Activation of complement system which leads to the production of C4 and its ultimate product, C4d, plays an important role in the pathogenesis of LN. Objectives: Although serum C4d levels correlate with disease activity, there is almost no study on the correlation between tissue deposition of C4d and classes of LN. Patients and Methods: Seventy-two patients with a diagnosis of SLE who met ≥ 4 criteria of American Rheumatism Association (ARA) were enrolled in this study. Blood levels of anti-nuclear antigens (ANA), anti-double stranded DNA (Anti-dsDNA), C3, C4 and antiphospholipid antibodies were measured. Renal tissue obtained by biopsy was examined regarding diffuse granular deposition of C4d along the glomerular capillary loops and classes of LN according to the World Health Organization (WHO) classification. Results: LN class IV was the most prevalent and LN class I had the least prevalence. There was no correlation between positive C4d staining and classes of LN (P>0.05), but a significant correlation between positive Anti-dsDNA and C4d positive LN was found (P=0.05). Likewise no correlation was detected between the low levels of complements and classes of LN or C4d positivity. Conclusions: The presence of C4d indicates activation of classical complement pathway in LN. C4d deposition in glomerular capillaries of LN does not indicate the present disease activity but may be a useful marker to predict the prognosis of LN. Anti-dsDNA is a valuable test for disease activity and is correlated with C4d positive staining.